Compound Passport Service: supporting corporate collection owners in open innovation - Andrews, David M.; Degorce, Sébastien L.; Drake, David J.; Gustafsson, Magnus; Higgins, Kevin M.; Winter, Jon J. (Drug discovery today, 2015)
•The trend towards open innovation means researchers face new problems tracking assets.•We borrow from social media concepts to solve these problems.•A SOA service is described that provides support and clarity to asset owners.•The accurate capture of metadata allows accurate asset rights management. A growing number of early discovery collaborative agreements are being put in place between large pharma companies and partners in which the rights for assets can reside with a partner, exclusively or jointly. Our corporate screening collection, like many others, was built on the premise that compounds generated in-house and not the subject of paper or patent disclosure were proprietary to the company. Collaborative screening arrangements and medicinal chemistry now make the origin, ownership rights and usage of compounds difficult to determine and manage. The Compound Passport Service is a dynamic database, managed and accessed through a set of reusable services that borrows from social media concepts to allow sample owners to take control of their samples in a much more active way.